2012
DOI: 10.14507/epaa.v20n3.2012
|View full text |Cite
|
Sign up to set email alerts
|

Re-Examining Exit Exams: New Findings from the Education Longitudinal Study of 2002

Abstract: Using the nationally representative, cohort-based data of the Education Longitudinal Study of 2002 (ELS:02), this study employs multiple regression to examine the effects of exit exams on student achievement and school completion. This study finds that exit exams as a whole do not have substantial effects on student achievement in mathematics, twelfth grade GPA, or school completion. Standards-based exams are a positive predictor of dropping out of school but lose their predictive power once GED recipients are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“… 3. Studies have indicated little practical difference between logit, probit, and linear regressions when the same dichotomous outcome variables were analyzed (Dey & Astin, 1993; Jepsen & Montgomery, 2012; Shuster, 2012). Since linear regression is easier to interpret (Angrist & Pischke, 2009), it was used to analyze the data for the current study. …”
mentioning
confidence: 99%
“… 3. Studies have indicated little practical difference between logit, probit, and linear regressions when the same dichotomous outcome variables were analyzed (Dey & Astin, 1993; Jepsen & Montgomery, 2012; Shuster, 2012). Since linear regression is easier to interpret (Angrist & Pischke, 2009), it was used to analyze the data for the current study. …”
mentioning
confidence: 99%
“…We pursue alternative route policy evaluation by addressing the research question: Does accounting for alternative route policies eliminate any observed negative effects of exit exam requirements on diploma attainment? This study uniquely contributes to the existing literature by (a) analyzing a recent data source that permits us to account for prior achievement, coursework requirements, and numerous additional personal and school factors potentially confounded with exit exam policies in determining graduation outcomes, (b) separating general education students from certain students with disabilities who are often subject to different graduation requirements, and (c) avoiding reliance on the questionable assumption (Jacob, 2001) that data on all variables, including the graduation outcome, is missing completely at random (see, e.g., Shuster, 2012) by implementing multiple imputation.…”
Section: Alternative Route Policies and Educational Attainmentmentioning
confidence: 99%
“…We use information from the CCD to devise a set of indicators for school locale and public/private status, and continuous measures of Grade 10 enrollment and minority student percentage. To characterize state economic climates, which might encourage or discourage high school completion and postsecondary enrollment, we control for the states' 2002 unemployment rate, reported by the U.S. Bureau of Labor Statistics, as well as the wage ratio of high school graduates to dropouts or Bachelor's degree recipients to high school graduates (Shuster, 2012), in the diploma acquisition and postsecondary enrollment models, respectively, drawn from U.S. Census 2000 data. We also distinguish statewide attainment levels by the percentage of residents over age 25 that held a Bachelor's degree in March 2002, from the Census Current Population Survey.…”
Section: Covariatesmentioning
confidence: 99%
“…Most of those states that adopted exit exams in the 2000's were standard-based type of exit exams. This coincided with the No Child Left Behind movement which saw many states use exit exams to satisfy the accountability purposes of NCLB (Shuster, 2012). The early adoptees were primarily few and were mostly minimum competency exit exams.…”
Section: State Adoption Of Exit Examsmentioning
confidence: 97%
“…Ever since its first annual report on exit exams published in 2002, it has published information that exposes achievement gaps in exit exams across the country (Center for Education Policy, 2005), and highlighted the effectiveness of alternative pathways to graduation for students who struggle to pass exit exams (Center for Education Policy, 2009). Other prominent studies have relied on this dataset to determine the effect of exit exams on mathematics achievement (Shuster, 2012), and effects on graduation rates (Caves & Balestra, 2016).…”
Section: The Primary Source For Information On Exit Exams Comes From Educationmentioning
confidence: 99%